The relationship between plasma aluminum content, lymphocyte DNA damage, and oxidative status in persons using aluminum containers and utensils daily - KOÇYİĞİT, ABDÜRRAHİM; Celik, Hakim; Celik, Necla; Kocyigit, ABDÜRRAHİM; Dikilitas, Murat (My University, 2012)
Objectives: The aim of this study was to explore the in vivo effect of the plasma aluminum content on lymphocyte DNA damage, the plasma protein carbonyl (PC) content, and malondialdehyde (MDA) and total antioxidative capacity (TAC) levels in aluminum exposed and non-exposed humans.